Potentiometric Characterization of Telomerase Activity Using a Copper(ii)-pyrophosphate Complex with a Copper ion-selective Electrode. (22nd January 2019) - Liu, Wen; Huang, Jiahua; Zhu, Yiming; Zhang, Huan; Ning, Ning; Song, Caiting
Abstract: A novel potentiometric sensing platform was designed for real-time electronic monitoring of telomerase activity using a copper(II) ion-selective electrode (Cu-ISE). The target-induced coordination of pyrophosphate ion with copper ion (Cu 2+ ) was utilized for the detection of the enzyme activity. Upon telomerase introduction, a DNA primer was elongated in the presence of deoxyribonucleoside triphosphates, accompanying formation of the by-product (pyrophosphate ion; P2 O7 4- ). The generated pyrophosphate ions chemically coordinated with free copper ions to form the copper(II)-pyrophosphate complex, thereby resulting in a decrease in the number of free copper ions present in solution. With the addition of telomerase, the electrode potential on the Cu-ISE increased relative to the background signal. The results indicated that the copper(II)-pyrophosphate system exhibited good potentiometric response for the detection of telomerase activity, and allowed the determination of the analyte in HeLa cell extract at concentrations as low as 36 cells mL −1 . Moreover, the Cu-ISE-based sensing platform afforded good reproducibility, thus representing a useful approach for practical use in quantitative telomerase activity assays.